Study design and rationale of "Synergistic Effect of Combination Therapy with Cilostazol and ProbUcol on Plaque Stabilization and Lesion REgression (SECURE)" study: a double-blind randomised controlled multicenter clinical trial - Ko, Young-Guk (BioMed Central, 2011)
BACKGROUND: Probucol, a cholesterol-lowering agent that paradoxically also lowers high-density lipoprotein cholesterol has been shown to prevent progression of atherosclerosis. The antiplatelet agent cilostazol, which has diverse antiatherogenic properties, has also been shown to reduce restenosis in previous clinical trials. Recent experimental studies have suggested potential synergy between probucol and cilostazol in preventing atherosclerosis, possibly by suppressing inflammatory reactions and promoting cholesterol efflux. METHODS/DESIGN: The Synergistic Effect of combination therapy with Cilostazol and probUcol on plaque stabilization and lesion REgression (SECURE) study is designed as a double-blind, randomised, controlled, multicenter clinical trial to investigate the effect of cilostazol and probucol combination therapy on plaque volume and composition in comparison with cilostazol monotherapy using intravascular ultrasound and Virtual Histology. The primary end point is the change in the plaque volume of index intermediate lesions between baseline and 9-month follow-up. Secondary endpoints include change in plaque composition, neointimal growth after implantation of stents at percutaneous coronary intervention target lesions, and serum levels of lipid components and biomarkers related to atherosclerosis and inflammation. A total of 118 patients will be included in the study. DISCUSSION: The SECURE study will deliver important information on the effects of combination therapy on lipid composition and biomarkers related to atherosclerosis, thereby providing insight into the mechanisms underlying the prevention of atherosclerosis progression by cilostazol and probucol. TRIAL REGISTRATION NUMBER: ClinicalTrials (NCT): NCT01031667